Social Disparity Reflected In Jane Austen's Mansfield Park (1814): A Sociological Perspective - Widya S, Ika, Dr. M. Thoyibi, MS., Siti Fatimah, S.Pd, M. Hum (2013)
The research is aimed to know the social disparity in Jane Austen "s Mansfield Park novel by using Sociological Perspective. Therefore, the study analyzes the novel in terms of it‟s structural elements and based on the sociological perspective. This research belongs to descriptive qualitative study. In this method, the writer uses two data sources; they are primary data and secondary data source. The primary data source and the object of this study is the novel Mansfield Park, meanwhile the secondary data sources are any books of literature and sociology and websites related to this study. The writer collects the data from both primary and secondary data sources in a short of document evidence. The study comes to the following conclusion. First, based on structural analysis, it is apparent that in Mansfield Park novel, Jane Austen conveys message that different lifestyle because of social classes. Second, it is clear that there is a close relation between this novel and the social reality of England in the early nineteenth century. Mansfield Park shows that the lives of the upper class were filled with luxurious, stands in sharp contrast with the lives of the lower class are shabby and uneducated.